The Influence of Organizational Culture On Employee Performance In Sukabumi City - Munandi Saleh (Journal of Governance, 2022)
Organizational culture in the sub-district environment will influence the behavior of organizational members so that it has an impact on employee performance. This study aims to determine the effect of organizational culture on employee performance in Gunungpuyuh District, Sukabumi City. In this study, a quantitative approach was used with the associative/relationship research method. The population in this study was all employees in the Gunungpuyuh District Office, Sukabumi City, totaling 26 people. The results showed that 16% of employee performance in Gunungpuyuh District, Sukabumi City, was influenced by Organizational Culture. An organizational culture based on an innovative work system needs to be developed at the Gunungpuyuh District Office, Sukabumi City. Thus, this innovative organizational culture model needs to be applied in an effort to improve the performance provided by employees.